Macroeconomic volatilities and the labor market: First results from the euro experiment - Christian Merkl; Tom Schmitz (Institute for the Study of Labor (IZA), 2010)
This paper analyzes the effects of different labor market institutions on inflation and output volatility. The eurozone offers an unprecedented experiment for this exercise: since 1999, no national monetary policies have been implemented that could account for volatility differences across member states, but labor market characteristics have remained very diverse. We use a New Keynesian model with unemployment to predict the effects of different labor market institutions on macroeconomic volatilities. In our subsequent empirical estimations, we find that higher labor turnover costs have a statistically significant negative effect on output volatility, while replacement rates have a positive effect, both of which are in line with theory. While labor market institutions have a large effect on output volatility, they do not seem to have much of an effect on inflation volatility, which can also be rationalized by our theoretical model.
Keywords: E24; E32; J20; 330; Labor market institutions; output and inflation volatility; labor turnover costs; unemployment benefits; unemployment; eurozone; Arbeitsmarktflexibilisierung; Makroökonomischer Einfluss; Arbeitslosigkeit; Konjunktur; Ungleichgewichtstheorie; Arbeitsmobilität; Kosten; Theorie; Europäische Wirtschafts- und Währungsunion; EU-Staaten